Cross-Infection Control Practices among Dental Undergraduates and Graduates in Prosthodontics- A Survey in Dental Colleges of Karachi - Muneeb Ahmed Lone; Bharat Kumar; Samina Kanwal; Farnaz Ilyas; Nadia Sultan; Zille-Huma; Maham Muneeb Lone (KARACHI MEDICAL AND DENTAL COLLEGE, 2022)
Objective: To assess the cross infection control practices among undergraduates and graduates working in the department of Prosthodontics in various public and private dental colleges of Karachi.  Methods: After approval from IRB, the self-administered questionnaire was sent via emails or social media platforms to undergraduate final year students and graduates currently working in Prosthodontics department of dental colleges of Karachi. Along with demographics, the questionnaire included close ended multiple-choice questions related to participants' practice regarding cross infection control. A reminder was sent after 2 weeks to help improve response rate. Statistical analysis was performed using SPSS 23.  Results: Out of total 617 respondents, there were 410(66.5%) final year dental students and 207(33.5%) house officers. Majority of participants 502(82.3%) had attended lecture regarding cross-infection control measures during their academic years, while only 178(28.8%) had attended hands-on workshops on the same. Majority 530(85.9%) recommended autoclave for sterilization for instruments. Almost all participants 603 (97.7%) wear gloves and perform hand hygiene 527(85.4%). More than two-thirds 416 (67.4%) respondents disinfect impressions, trial wax dentures, bite registrations and metal trials before sending to the dental laboratory. Almost 50% of the participants did not disinfect plastic impression trays, shade guide, rubber bowl, wax knife, carver and spatula in between patients.  Conclusion: Results of this study highlight the need of re-emphasizing cross-infection control measures and practices in the Prosthodontics OPD. Strict administrative protocols should be set to implement cross-infection control practices. Lectures and hands-on workshops regarding cross-infection control, disinfection and sterilization should be a mandatory part of curriculum and be reiterated in continuing dental education seminars.